2006
DOI: 10.1088/0031-9155/51/10/015
|View full text |Cite
|
Sign up to set email alerts
|

A fit method for the determination of inherent filtration with diagnostic x-ray units

Abstract: A method for the determination of total inherent filtration for clinical x-ray units using attenuation curves was devised. A model for the calculation of x-ray spectra is used to calculate kerma values which are then adjusted to the experimental data in minimizing the sum of the squared relative differences in kerma using a modified simplex fit process. The model considers tube voltage, voltage ripple, anode angle and additional filters. Fit parameters are the thickness of an additional inherent Al filter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…Then we found accurate values of inherent filtration and anode roughness for this new dataset using experimental attenuation values, with an approach similar to the one presented in Ref. 29. The estimated value of differential inherent filtration between the radiology and mammography datasets was found to be of 1.68 mm Al, in line with the value of inherent filtration reported by Boone et al, who obtained a value of ∼2.0 mm Al for the Fewell spectra, computed as the nominal 1.1 mm Al plus an extra filtration of ∼0.88 mm (for voltages between 30 and 40 kV) which was necessary to match measured attenuation.…”
Section: Discussionmentioning
confidence: 75%
“…Then we found accurate values of inherent filtration and anode roughness for this new dataset using experimental attenuation values, with an approach similar to the one presented in Ref. 29. The estimated value of differential inherent filtration between the radiology and mammography datasets was found to be of 1.68 mm Al, in line with the value of inherent filtration reported by Boone et al, who obtained a value of ∼2.0 mm Al for the Fewell spectra, computed as the nominal 1.1 mm Al plus an extra filtration of ∼0.88 mm (for voltages between 30 and 40 kV) which was necessary to match measured attenuation.…”
Section: Discussionmentioning
confidence: 75%
“…49 Furthermore, comparisons between measured and calculated air kerma using Birch and Marshall-based codes have demonstrated an overestimation of calculated kerma. 33,50 Ay et al 37 reported on average overestimation of 9.5%-14.4% for kerma derived using XCOMP5R for tube voltages from 80 to 120 kV, 12.5°tungsten target and 1.2 mm Al inherent filtration, whereas MCNP4C resulted in estimates between 2.0 and 4.4%. By invoking MCNP's GEB card along with PHYS card, a useful card for biasing some physical parameters, the bias will certainly be further reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a variation of about 0.2 mm Al in HVL for an anode roughness of 5 m at 70 kVp and 2.5 mm Al filtration was determined semiempirically. 32 The same group reported that anodes with a surface roughness of about 1.4-3.8 m correspond to additional filtration by tungsten with a thickness of 2.12-8.21 m. 33 Other investigators presented detailed measurements of anode surface profiles of 19 diagnostic x-ray tubes and predicted empirically an intensity loss of 4% for rough anodes with 8 m deep cracks. 34 Although Monte Carlo simulation has experienced considerable growth both in terms of number of articles and diversity of studies, 35 to the best of the authors' knowledge, this is the first attempt to address the issue of anode roughening as a factor influencing x-ray spectra through MC modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Először Nowotny [5] vizsgálta a felületi érdesség hatását a BM modell [12] segítségével. Meghzifene [23] az anód anyagából készült szűrő segítségével próbálta leírni a felületi érdesség hatását.…”
Section: A Felületi éRdesség éS Hatásainak Modellezéseunclassified
“…A 6. ábra mutatja az illesztési módszer által kapott air kerma értékek relatív hibáját, [23]. Az adatok először csőfeszültség szerint lettek csoportokba rendezve, majd az egyes csoportokon belül szűrővastagság szerint.…”
Section: Meghzifene Illesztési Módszereunclassified